Lessons from Lucy : the simple joys of an old, happy dog - Barry, Dave (New York : Simon & Schuster, 2019)
Faced with the obstacles and challenges of life after middle age, Pulitzer Prize-winning columnist Dave Barry turns to his best dog, Lucy, to learn how to live his best life. From "Make New Friends" (an unfortunate fail when he can't overcome his dislike for mankind) to "Don't Stop Having Fun" (validating his longtime membership in a marching unit that performs in parades -- and even Obama's inauguration), Dave navigates his later years with good humor and grace. Lucy teaches Dave how to live in the present, how to let go of daily grievances, and how to feel good in your own skin. The lessons are drawn from Dave's routine humiliations and stream-of-consciousness accounts of the absurdities of daily life. Whether he's trying to "Pay Attention to the People You Love" (even when your brain is not listening) or deciding to "Let Go of Your Anger," Dave Barry's Lessons From Lucy is a witty and wise guide to joyous living--
107031
Keywords: Barry, Dave; Conduct of life -- Humor; Aging -- Humor; Pets -- Humor; Human-animal relationships; .; Humor